Molecular characterisation of Cryptosporidium spp. in lambs in the South Central region of the State of São Paulo - A.S. Zucatto; M.C.C. Aquino; S.V. Inácio; R.N. Figueiredo; J.C. Pierucci; S.H.V. Perri; M.V. Meireles; K.D.S. Bresciani (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2015)
Considering the proximity of sheep farmers to animals that are possibly diseased or releasing fecal oocysts into the environment and the marked pathogenicity in lambs, the aim of this study was to determine the occurrence and to molecularly characterize the infection by Cryptosporidium spp. in lambs in the South Central region of the state of São Paulo, Brazil. A total of 193 fecal samples were collected from sheep of several breeds, males and females, aged up to one year. Polymerase chain reaction (nested-PCR) was used to amplify DNA fragments from the subunit 18S rRNA gene and indicated 15% positivity; sequencing of amplified fragments was possible for 19 samples. Analysis of the obtained sequences showed that the identified species were Cryptosporidium xiaoi for 15 samples, constituting thus the first molecular characterization study of this Cryptosporidium species in Brazil. Cryptosporidium ubiquitum was identified for three samples and Cryptosporidium meleagridis for one sample; the latter two are considered zoonotic species.